(untitled) (Journal of Economic Research & Business Administration, 2015)
Budgeting – covers all aspects of economic activity. Budgeting process provides ongoing monitoring of decisions and procedures to ensure the achievement of the planned financial performance. University budget - is financial, quantified expression plan of it economically sustainable development in order to achieve its goals. Creation and implementation of budgeting system allows the university to improve governance and transparency, introduce a strict accounting and control spending and optimize costs.